Metal cutting theory and cutting tool design : - Arshinov, Vasilii Andreevich (Mir Publishers, 1976)
The metal parts of machine, instruments and other articles are produced by casting molten metal into moulds, by mechanical working(rolling, forging and pressworking), by electrical and chemical machinign methods, and by metal cutting. The metal cutting process consits in removing a layer of metal from the blank to to obtain a machine part of the requiried shape and dementions, and with the specified quality of surface finish.